Modeling of train flow handling through a limiting single-track section of the route at the organization of high-speed operation using the existing infrastructure - S. V. Karasev; A. D. Kalidova (Вестник Научно-исследовательского института железнодорожного транспорта)
The article examines the problem of studying the process of handling the opposing train flows through a single track section of the route by modeling for the conditions of organizing high-speed operation while minimizing capital investments in infrastructure. The issue of saving capital investments in infrastructure is especially urgent with the small size of high-speed traffic on non-main lines, including feeder lines for high-speed routes. Significant savings can be ensured by using single-track fixed structures, as well as single-track distances in conditions where the construction of the second main track is associated with a significant increase in cost. However, in this case, an important question arises about the effect of high-speed traffic on the capacity of single-track sections and on the line as a whole. When operating a one-track or two-track section of the route, the issue arises on the adequacy of the capacity level of the junction points from two to one track (one-track section of the route, then the limiting element), and also the possible delays of trains. To investigate the conditions for passing trains through such sections of the route, the Barrier-1 program was developed, which makes it possible to estimate the capacity of the limiting element on the basis of the methods of queuing theory. The model implements an algorithm that does not impose any restrictions on the characteristics of the incoming train flow, which makes it possible to investigate the various conditions for trains to pass through the limiting element (in particular, the regularity or irregularity of the flow, the intervals between trains, the occupation times of the limiting element). The results of modeling the passing of counter traffic flows are displayed in numerical form, as well as in the form of the train traffic schedule, taking into account the increase in time on approaches to the limiting element. The model takes into account the peculiarities of passing the opposing train traffic and allows determining optimal way of passing high-speed and other trains through the limiting element of the route. The calculation is provided using the model and analysis of the capacity of a limiting element of the route for various options of the high-speed trains handling organization, as well as the conditions under which the maximum capacity with the minimum number and delay time (decrease) of trains on approaches to the limiting element.